Izidor Cankar and the Royal Yugoslav Legation in Buenos Aires - Rahten, Andrej (Two Homelands, 2009)
The article discusses activities of the Slovenian diplomat Dr. Izidor Cankar at the diplomatic representation of the Kingdom of Yugoslavia in Buenos Aires in the period 1936–1942. The research of his activities is based on sources from the archives in Ljubljana and Belgrade, with a particular focus on his correspondence with leading Slovene politicians on the eve of the Second World War and during the War itself. Cankar asserted himself as a self-confident diplomat, while at the same time being the first Yugoslav envoy to set as a priority concern for the Slovene emigrants from the Primorska region.